The Origin of the Energy - Carmesin, Hans-Otto (PhyDid B - Didaktik der Physik - Beiträge zur DPG-Frühjahrstagung, 2021)
The energy is an essential basic concept of physics. Additionally, the mass is included, as it is equivalent to energy. Moreover the energy is constant in the time evolution of the universe. So the question arises: What is the origin of the energy. Using general relativity and quantum physics, we determine that origin. Moreover I report about experience with that topic in a research club and in university courses.